Anhedonia and depressive symptoms in adolescent university students from china: the mediating role of early perceive stress - Taipeng Sun; Pan Liu; Sulin Shan; Yan Ren; Zhi Zhen; Gang Chen; Lihua Jiang (BMC Public Health)
Abstract Background The coronavirus disease 2019 (COVID-19) pandemic has caused increased psychological problems in Group-living people, such as university students. The current epidemic of COVID-19 has become the new normal. The more tailored approach focused on Triggers and key points of emotion regulation may be helpful for the mental health of group-living people. Objective This study aims to investigate the prevalence of symptoms of Depression, Anxiety, Anhedonia, and Perceived Stress. Further analyses were used to find their risk factors and their inter-relationships. Methods An online, cross-sectional survey was undertaken with university students from five universities in China by The Depression Anxiety Stress Scales (DASS), Perceived Stress Scale (PSS), and Snaith-Hamilton Pleasure Scale (SHAPS). The Mann-Whitney U test was used to analyze differences between male and female students. Multiple linear regression analysis was applied to examine the related factors of anhedonia. Additionally, multigroup mediation models were used to analyze the relationship between perceived stress, anhedonia, stress, and depression. Results A total of 3,568 valid questionnaires were returned, and 814 (22.81%) with mild to moderate depressive symptoms, 114 (3.20%) with severe depressive symptoms; 840 (23.54%) with mild to moderate anxiety, and 235 (6.59%) with severe anxiety; 366 (10.26%) with mild to moderate stress, and 80 (2.24%) with severe stress. Interestingly, the levels of stress, anxiety, and anhedonia were higher in female students than in male students. The Multiple linear regression showed that anhedonia scores were correlated with PSS scores, DASS-depression scores, and females. Perceived Stress plays a negative mediating role between DASS-stress and anhedonia. Furthermore, Perceived Stress also plays a negative mediating role between stress and depression, but this effect was present only in individuals with mild to moderate depression. Conclusion The finding of this cross-sectional study suggested that there were high prevalence rates of depression and anxiety symptoms in university students from China during the COVID-19 new normal. Early perceived stress was associated with the progress of depression and anhedonia.